2016
DOI: 10.14503/thij-14-4792
|View full text |Cite
|
Sign up to set email alerts
|

Primary Cardiac Sarcoidosis with Syncope and Refractory Atrial Arrhythmia: A Case Report and Review of the Literature

Abstract: We discuss the case of a 38-year-old 3 Sarcoidosis is most often associated with the lungs, but the disease can manifest itself in any tissue. Cardiac involvement was not described until 1929. 4,5 In recent times, cardiac manifestations have been understood to play a greater role in sarcoidosis morbidity than previously thought. In this report, we present a case of primary cardiac sarcoidosis that was successfully treated with a hybrid pharmacologic, surgical, and catheterbased intervention. Case ReportA 38-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Various studies have reported a higher incidence of supraventricular arrhythmias in patients with biphasic P wave in the inferior leads [ 26 , 27 ]. Since cardiac sarcoidosis is associated with an increased incidence of atrial arrhythmias, including atrial fibrillation [ 7 , 28 ], the greater prevalence of biphasic P wave may be a harbinger of atrial arrhythmias in sarcoidosis. The more vertical orientation of lead III as compared to the other inferior leads could explain the early appearance of biphasic P waves in this lead.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have reported a higher incidence of supraventricular arrhythmias in patients with biphasic P wave in the inferior leads [ 26 , 27 ]. Since cardiac sarcoidosis is associated with an increased incidence of atrial arrhythmias, including atrial fibrillation [ 7 , 28 ], the greater prevalence of biphasic P wave may be a harbinger of atrial arrhythmias in sarcoidosis. The more vertical orientation of lead III as compared to the other inferior leads could explain the early appearance of biphasic P waves in this lead.…”
Section: Discussionmentioning
confidence: 99%
“…An estimated 20–25% of patients with pulmonary/systemic sarcoidosis have asymptomatic cardiac involvement (clinically silent disease). About 40–50% of patients who die of sarcoidosis-related complications are found to have cardiac sarcoidosis at necropsy despite never having manifested any clinical evidence of myocardial involvement during their lifetime [ 6 , 7 ]. The predominant sites of myocardial involvement, in decreasing order of frequency, are the left ventricular free wall and papillary muscles, the basal aspect of the ventricular septum, the right ventricular free wall, and the atrial walls [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Black men are second highest at 29.8 per 100 000. White women and men have rates of 12.1 and 9.6 cases per 100 000, revealing a clear racial predilection [2]. …”
Section: Discussionmentioning
confidence: 99%
“…Few reports have proved the presence of granuloma lesions in the atria in patients with cardiac sarcoidosis in a direct way. 19) In many cases, atrial involvement of cardiac sarcoidosis has been found on the basis of diagnostic imaging of the atria, histological findings of other organs, and clinical findings. No studies have assessed images of atrial legions in CS in a systemic manner.…”
Section: Diagnostic Imaging Of Atrial Lesionsmentioning
confidence: 99%